LINGUISTICS AND PHYSICS: MUTUAL RELATIONS AND FASCINATION - SteciÄ…g, Magdalena (European Scientific Journal, ESJ, 2013)
The aim of the paper is to present diverse and multidirectional relationships between the two disciplines which are apparently only distantly related to each other - physics and linguistics. Mutual fascination results from the concern to describe the "physical world" the most adequately using the language in which it is sometimes difficult to express new cognitive ideas and inaccessible to the average language user reality that is based not on accepted rules of common sense thinking and speaking. Three moments that were breakthrough in the development of science, which show the connections between discoveries in physics and linguistic developments, will be analysed in the main part. In the conclusion the attempts to get closer the worldview contained in the (SAE) language and the image emerging from contemporary physical experiments will be briefly evaluated.